Management of intra-abdominal infections: recommendations by the WSES 2016 consensus conference - Sartelli, Massimo; Catena, Fausto; Abu-Zidan, Fikri M; Ansaloni, Luca; Biffl, Walter L; Boermeester, Marja A; Ceresoli, Marco; Chiara, Osvaldo; Coccolini, Federico; De Waele, Jan J; Di Saverio, Salomone; Eckmann, Christian; et al. (World journal of emergency surgery, 2017)
This paper reports on the consensus conference on the management of intra-abdominal infections (IAIs) which was held on July 23, 2016, in Dublin, Ireland, as a part of the annual World Society of Emergency Surgery (WSES) meeting. This document covers all aspects of the management of IAIs. The Grading of Recommendations Assessment, Development and Evaluation recommendation is used, and this document represents the executive summary of the consensus conference findings.
Keywords: výsledek terapie; Ultrasonography; Decision Support Techniques; Appendectomy; metody pro podporu rozhodování; počítačová rentgenová tomografie; nitrobřišní infekce; směrnice jako téma; antibakteriální látky; cholecystektomie laparoskopická; laparoskopie; Sepsis; Peritonitis; Treatment Outcome; Tomography, X-Ray Computed; bolesti břicha; lidé; nitrobřišní hypertenze; Cholecystectomy, Laparoscopic; Anti-Bacterial Agents; apendektomie; Humans; vyhodnocení orgánové dysfunkce; Intraabdominal Infections; Antibiotics; Abdominal Pain; Laparoscopy; Diverticulitis; Intra-abdominal infections; Organ Dysfunction Scores; Intra-Abdominal Hypertension; divertikulitida; Guidelines as Topic; ultrasonografie